1994
DOI: 10.1007/3-540-58233-9_13
|View full text |Cite
|
Sign up to set email alerts
|

Comparing combinatory reduction systems and higher-order rewrite systems

Abstract: Abstract. In this paper two formats of higher-order rewriting are compared: Combinatory Reduction Systems introduced by Klop and Higherorder Rewrite Systems defined by Nipkow. Although it always has been obvious that both formats are closely related to each other, up to now the exact relationship between them has not been clear. This was an unsatisfying situation since it meant that proofs for much related frameworks were given twice. We present two translations, one from Combinatory Reduction Systems into Hig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

1994
1994
2007
2007

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 14 publications
0
19
0
Order By: Relevance
“…Our syntax is inspired by CRSs, but similar results can be obtained by using other higher-order systems, such as Nipkow's Higher-order Rewrite Systems [22], or Khasidashvili's Expression Reduction Systems [13]. The three formalisms are closely related [26]. CRSs have been used in previous work on interaction nets: Laneve [20] defined Interaction Systems as CRSs, and in [7] a translation function is given from interaction nets to CRSs.…”
Section: Introductionmentioning
confidence: 89%
“…Our syntax is inspired by CRSs, but similar results can be obtained by using other higher-order systems, such as Nipkow's Higher-order Rewrite Systems [22], or Khasidashvili's Expression Reduction Systems [13]. The three formalisms are closely related [26]. CRSs have been used in previous work on interaction nets: Laneve [20] defined Interaction Systems as CRSs, and in [7] a translation function is given from interaction nets to CRSs.…”
Section: Introductionmentioning
confidence: 89%
“…Hence it is a β-IDTS. In [31], van Oostrom and van Raamsdonk studied this translation in detail and proved:…”
Section: Application Of the General Schema To Hrssmentioning
confidence: 96%
“…In particular, it has been shown that crss and hrss have the same expressive power and therefore they can be considered equivalent [21]. Using this comparison, we can have an indirect representation of the ρ-calculus into hrss that is based on the translation from the crss to hrss and the translation from ρ-calculus to crss we have defined in this paper.…”
Section: Discussionmentioning
confidence: 99%
“…By the encoding of Section 3.1, Lemma 5 and the confluence results for orthogonal crss (see for example [20,21]). …”
Section: Corollary 1 (Confluence) the ρ-Calculus With Linear Algebramentioning
confidence: 99%
See 1 more Smart Citation